Experimental evaluation of heat flow from rectangular fins array under forced convection - Shahrizal, Ibrahim (2012)
The application of fins is to reduce heat from an object. The experiment is about utilizing the fins for heat dissipation. The method is by using an experimental set-up to observe temperature difference of 6 arrays of rectangular fins and calculate the Nusselt number to understand the convection force of the fins and validate the data with theoretical calculation from the experimental result. Second approaches are by wrapping each of the fins with aluminum coil and compare the result with experimental result without the wrap. Conclusion, it is observed that the highest value for the Nusselt number is 505.469 can be achieved by the wrapped fins array than without wrap on fins about 39.347 which is about 8.44% positive increment. Further research can be done through used of custom made fins in shape of aerofoil, which perhaps help in heat dissipation of the fins much better as the air flow is much smoother.